Islam di Kalimantan Selatan pada Abad Ke-15 sampai Abad Ke -17 - Muhammad Azmi (Program Studi Pendidikan Sejarah FKIP Universitas Mulawarman, 2017)
The theory of the process of the coming of Islam to Indonesia have been assessed and expressed by many experts. Stages of the process in Nusantara is divided into three phases, the process of arrival in the 7th century, the deployment process in the 11th century and the process of development in the 13th century. It also gives influence on the process of arrival, distribution and development of Islam in South Kalimantan. This paper is a review of the literature that gives an overview on the islamization of the South Kalimantan covering the arrival, distribution and development at the 15th century until the 17th century.